Pengaruh Beban Pajak Tangguhan, Profitabilitas, dan Leverage Terhadap Manajemen Laba - Muhammad Satrio Wibisono; Nuramalia Hasanah; Hafifah Nasution; I Gusti Ketut Agung Ulupui; Indah Muliasari (Department of Accounting, Faculty of Economics & Business, 2022)
This study aims to determine the effect of deferred tax expense, profitability, and leverage. The independent variables used in this study are deferred tax expense, profitability and leverage. The dependent variable used in this study is earnings management. This study uses secondary data, namely financial statements and annual reports of companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period with a total of 84 observations. The sampling method used in this study is the purposive sampling method. This study uses multiple linear regression analysis which is processed using the SPSS 26 application. The results show that deferred tax expense has no effect on earnings management. Profitability has a positive effect on earnings management. Leverage has a negative effect on earnings management.